Adolescents who Perceive their Diet as Healthy Consume More Fruits, Vegetables and Milk and Fewer Sweet Drinks - Davenport, Leigh Anna; Radcliffe, John; Chen, Tzu An; Cullen, Karen W (International Journal of Child Health and Nutrition, 2014)
This study assessed whether adolescents’ perception of the healthfulness of their diet was related to dietary behaviors over the past week, controlling for demographic characteristics. Participants (n=391) completed an online survey on the frequency of specific dietary behaviors over the past week and the perceived healthfulness of their own diet compared to their peers’ diets. Mean intakes of juice, fruit, vegetables, milk, sugar-sweetened beverages, and diet beverages, were compared by perceived healthfulness of diet categories using analysis of covariance. Participants with higher perceived healthfulness of diet reported significantly higher mean fruit and vegetable intakes and a lower mean intake of sugar sweetened beverages over the past week than participants with the same or lower perceived healthfulness of diet (all p< 0.001). Participants who reported a higher perceived healthfulness of diet reported a significantly higher frequency of milk intake (p< 0.05) than those who reported the same perceived healthfulness of diet. Those with lower perceived healthfulness of diet reported higher mean frequencies of diet beverage intakes than those with higher perceived healthfulness (p<0.05). Further research should include qualitative studies with adolescents to explore how individuals rate their diets and how these perceptions influence dietary choices.